Person-Centered Supervision: A Realistic Approach to Practice Within Counselor Education - Lindsay P Talley; Leslie Jones (Teaching and Supervision in Counseling, 2019)
In a counselor’s development, supervision is a necessary and integral part of the process to forming a professional counseling identity. Just as multiple counseling theories exist to provide a conceptual framework for the process, so too do multiple supervision theories exist to help guide the supervision experience. Based upon the work of Carl Rogers, a person-centered approach to supervision centers on two main themes: the process and the relationship (Rice, 1980). Throughout this article, the themes of process and relationship as well as the fit of person- centered supervision within a counselor education program are explored. A case example is also provided to further illustrate person-centered supervision within a counselor education program. Although more literature is needed to further discuss operating from a person-centered perspective within counselor education, this theoretical approach provides enough support and flexibility to work as a guiding theory for supervisors within counselor education programs.
Keywords: Person-Centered; Supervision; Counselor Education